Malta Negotiation (02.12.1989), National Heros and Perspective of Georgia - Putkaradze, Tariel (Actual Problems of Kartvelology, 2019)
The failure of the soviet ideology and economic system (partly thanks to R. Reagan’s wise policy) in 1980s, paved the way for successful modernization of the soviet empire. The last stage of this process, covering the period 1985-1991, went down in history with the name Perestroika (“restructuring” in Russian). The finale of Perestroika was the agreement reached during the Malta Summit of December 2, 1989. Based on that agreement, in September 1991 the Soviet Union ceded the Easter Europe and three Baltic republics to the West. Russia used Malta Summit as an excuse for using armed forces to overthrow the Georgian Government that announced independence. In 1992-1993, the overthrow of Georgia’s legitimate government was followed by grave results for Georgia. Particularly, in Abkhazia and Tskhinvali region – historical territories of Georgia – the armed formations of the Russian Empire committed genocide of Georgian people and ousted the survivors resisting the Russian occupation (regardless of their ethnic origin: Georgians, Abkhazians, Russians, Armenians…) from those territories (turning more than 400 000 people into IDPs). The civilized world should make an impartial assessment of the aggression committed by Russia in the Caucasus in 1990s; it is time to lay bare the true essence of the 1992-1993 coup d’état and the conflicts going in Abkhazia and Tskhinvali: both times, in 1991-1992 and in 2008, Russia punished Georgia for announcing independence and making a pro-western choice. What we are facing in Abkhazia and Tskhinvali region – historical districts of Georgia – are not “ethnic conflicts”, but the war Russia has been waging against Georgia since December 22, 1991, for its orientation to the civilized west. Great figures can influence public awareness even after their death. Since 1970s, Zviad Gamsakhurdia and Merab Kostava had been leading the national-liberation movement to achieve the goal they had set – to restore the independence of the Republic of Georgia, which had been lost in 1921; to ensure protection of human rights and to preserve and develop the Georgian culture. During the last 45 years, Georgia made significant steps in that direction (a referendum, de jure restoration of independence, the status of occupant give to the Russian army, a plebiscite on NATO membership etc.). However, the struggle is not over yet: the fifth part of Georgian territory continues to be occupied by the Russian Empire, human rights are still violated and the Georgian identity is still at risk… Thus, there are more issues on the agenda, which need to be addressed. In this respect, it is significant to consider the policy pursued by Zviad Gamsakhurdia and Merab Kostava and to appreciate their self-sacrifice in the fight against the Russian Empire. Unfortunately, attempts are still made to discredit their names and distort their statements. Therefore, in the near future the educational system and the new political spectrum of Georgia need to advance the true guiding principles of Zviad Gamsakhurdia and Merab Kostava and to draw the attention of wide public and international community to those principles. Only through the correct political strategy and the support of international community is it possible to ensure the full de-occupation of Georgia, establishment of state institutions and successful completion of the 50-year-old national-liberation movement.